Synthesis of an Indoloquinoxaline Derivative as Potential Inhibitor of InhA enzyme of Mycobacterium tuberculosis - Zanzoul, Asmae; Chollet, Aurélien; Piedra-Arroni, Estefania; Stigliani, Jean-Luc; Bernardes-Génisson, Vania; Essassi, El Mokhtar; Pratviel, Geneviève (Letters in Organic Chemistry, 2015)
Seven heterocyclic compounds derived from isatin have been synthesized. Isatin was N-substituted with four aromatic/aliphatic and benzylic moieties (1a-d). Compounds 1a-c were condensed with o-phenylenediamine to afford indoloquinoxaline derivatives (2a-c). Products were tested as inhibitors of InhA enzyme of M. tuberculosis. Compound 6-(diethylaminoethyl)indoloquinoxaline (2a) inhibited 38% of InhA activity at 50 µM. The possible modes of interaction of 2a with InhA were explored by molecular docking. Docking experiments afford keys to improve compound 2a for the design of new potential active drugs against tuberculosis.
Keywords: Heterocyclic compounds